Stress induced proinflammatory adaptations: Plausible mechanisms for the link between stress and cardiovascular disease - Slusher, Aaron L.; Acevedo, Edmund O. (Frontiers in Physiology, 2023)
Initiating from Hans Selye’s conceptualization of stress physiology, to our present understanding of allostatic load as the cumulative burden of chronic psychological stress and life events, investigators have sought to identify the physiological mechanisms that link stress to health and disease. Of particular interest has been the link between psychological stress and cardiovascular disease (CVD), the number one cause of death in the United States. In this regard, attention has been directed toward alterations in the immune system in response to stress that lead to increased levels of systemic inflammation as a potential pathway by which stress contributes to the development of CVD. More specifically, psychological stress is an independent risk factor for CVD, and as such, mechanisms that explain the connection of stress hormones to systemic inflammation have been examined to gain a greater understanding of the etiology of CVD. Research on proinflammatory cellular mechanisms that are activated in response to psychological stress demonstrates that the ensuing low-grade inflammation mediates pathways that contribute to the development of CVD. Interestingly, physical activity, along with its direct benefits to cardiovascular health, has been shown to buffer against the harmful consequences of psychological stress by “toughening” the SAM system, HPA axis, and immune system as “cross-stressor adaptations” that maintain allostasis and prevent allostatic load. Thus, physical activity training reduces psychological stress induced proinflammation and attenuates the activation of mechanisms associated with the development of cardiovascular disease. Finally, COVID-19 associated psychological stress and its associated health risks has provided another model for examining the stress-health relationship.